Dietary Influence on Depression. Issue 5 (September 2016) - Morin, Karen H.
Abstract : Food can influence mental wellbeing, making a nutritional assessment a critical aspect of nursing practice. Our nutrition expert, Dr. Morin, explains the potential link between diet and depression.